Effects of a healthy lifestyle intervention and COVID-19-adjusted training curriculum on firefighter recruits - Lan, Fan Yun; Scheibler, Christopher; Hershey, Maria Soledad; Cabrera, Juan Luis Romero; Gaviola, Gabriel C.; Yiannakou, Ioanna; Fernandez-Montero, Alejandro; Christophi, Costas A.; Christiani, David C.; Sotos-Prieto, Mercedes; Kales, Stefanos N. (My University, 2022)
There are knowledge gaps regarding healthy lifestyle (HLS) interventions in fire academy settings and also concerning the impacts of the pandemic on training. We enrolled fire recruits from two fire academies (A and B) in New England in early 2019 as the historical control group, and recruits from academies in New England (B) and Florida (C), respectively, during the pandemic as the intervention group. The three academies have similar training environments and curricula. The exposures of interest were a combination of (1) an HLS intervention and (2) impacts of the pandemic on training curricula and environs (i.e. social distancing, masking, reduced class size, etc.). We examined the health/fitness changes throughout training. The follow-up rate was 78%, leaving 92 recruits in the historical control group and 55 in the intervention group. The results show an HLS intervention improved the effects of fire academy training on recruits healthy behaviors (MEDI-lifestyle score, 0.5 ± 1.4 vs. - 0.3 ± 1.7), systolic blood pressure (- 7.2 ± 10.0 vs. 2.9 ± 12.9 mmHg), and mental health (Beck Depression score, - 0.45 ± 1.14 vs. - 0.01 ± 1.05) (all P < 0.05). The associations remained significant after multivariable adjustments. Moreover, a 1-point MEDI-lifestyle increment during academy training is associated with about 2% decrement in blood pressures over time, after multivariable adjustments (P < 0.05). Nonetheless, the impacts of pandemic restrictions on academy procedures compromised physical fitness training, namely in percent body fat, push-ups, and pull-ups.
Keywords: COVID-19; Curriculum; Exercise Test; Firefighters; Healthy Lifestyle; Humans; Physical Fitness